Texture evolution in shocked Ni47Ti44Nb9 shape memory alloys. (December 2013) - Liu, H; Sun, G; Wang, Y; Chen, B; Tian, Q; Wang, X; Zhang, C
Abstract : The shock loading experiments on Ni47 Ti44 Nb9 shape memory alloys were performed using the single stage gas gun under various shock conditions. The texture evolution of the shocked specimens was investigated. The results show that the initial sheet textures of 111 < > and 111 < > gradually evolve into 111 plane texture after shock loading. Meanwhile, a weak texture component 001 is also observed in all the shocked specimens, indicating that the recovery strains in shocked specimens decrease. Moreover, the evidence for the texture inheritance in the austenite and martensite phases of Ni47 Ti44 Nb9 alloys was also provided in this present work.